Direct Admission of Patients With ST‐Segment–Elevation Myocardial Infarction to the Catheterization Laboratory Shortens Pain‐to‐Balloon and Door‐to‐Balloon Time Intervals but Only the Pain‐to‐Balloon Interval Impacts Short‐ and Long‐Term Mortality - Simcha R. Meisel; Michael Kleiner‐Shochat; Rami Abu‐Fanne; Aaron Frimerman; Asaf Danon; Sa’ar Minha; Yaniv Levi; Alex Blatt; Jameel Mohsen; Avraham Shotan; Ariel Roguin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Shortening the pain‐to‐balloon (P2B) and door‐to‐balloon (D2B) intervals in patients with ST‐segment–elevation myocardial infarction (STEMI) treated by primary percutaneous coronary intervention (PPCI) is essential in order to limit myocardial damage. We investigated whether direct admission of PPCI‐treated patients with STEMI to the catheterization laboratory, bypassing the emergency department, expedites reperfusion and improves prognosis. Methods and Results Consecutive PPCI‐treated patients with STEMI included in the ACSIS (Acute Coronary Syndrome in Israel Survey), a prospective nationwide multicenter registry, were divided into patients admitted directly or via the emergency department. The impact of the P2B and D2B intervals on mortality was compared between groups by logistic regression and propensity score matching. Of the 4839 PPCI‐treated patients with STEMI, 1174 were admitted directly and 3665 via the emergency department. Respective median P2B and D2B were shorter among the directly admitted patients with STEMI (160 and 35 minutes) compared with those admitted via the emergency department (210 and 75 minutes, P<0.001). Decreased mortality was observed with direct admission at 1 and 2 years and at the end of follow‐up (median 6.4 years, P<0.001). Survival advantage persisted after adjustment by logistic regression and propensity matching. P2B, but not D2B, impacted survival (P<0.001). Conclusions Direct admission of PPCI‐treated patients with STEMI decreased mortality by shortening P2B and D2B intervals considerably. However, P2B, but not D2B, impacted mortality. It seems that the D2B interval has reached its limit of effect. Thus, all efforts should be extended to shorten P2B by educating the public to activate early the emergency medical services to bypass the emergency department and allow timely PPCI for the best outcome.